Implementasi Program Merdeka Belajar dalam Meningkatkan Kualitas Pendidikan di Sekolah Dasar - Wildan Nuril Ahmad Fauzi (Al Banin : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study analyzes the implementation of the "Merdeka Belajar" program in the context of national education transformation in Indonesia. This program aims to improve the quality of education through freedom of thought and autonomy in the learning process. The method used is a literature study by collecting and evaluating various sources such as scientific journals, books, research reports, and policy documents. The results show that "Merdeka Belajar" gives teachers greater freedom in designing innovative learning methods that suit students' needs. This freedom is proven to increase student motivation and engagement, and shape students' characters to be more independent, critical, and adaptive. In addition, the program also contributes to improving teacher professionalism and creating a conducive learning environment. Despite facing challenges such as curriculum adjustments and limited resources, continued support from the government and stakeholders is needed. The "Merdeka Belajar" program has great potential to transform national education and prepare the younger generation for future global challenges.